Faktor yang Mempengaruhi Perilaku Konsumen Terhadap Keputusan Konsumen dalam Memilih Tempat Wisata Air Terjun Di Desa Bonepuso Kecamatan Bulagi Selatan: Factors Affecting Consumer Behavior on Consumer Decisions in Choosing Waterfall Tourist Attractions in Bonepuso Village South Bulagi District - Hermin Kuongomo; Heny Ariwijaya; Sri Mulyaningsih Kamaru (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2020)
This research aims to determine how the influence of consumer behavior factors consisting of cultural factors, social factors, personal factors, and psychological factors on consumer decisions in choosing Batualambung Waterfall tourist attractions. The analytical method used in this study is multiple linear regression analysis using 80 samples taken using the accidental sampling technique. Based on the study results, consumer behavior factors consist of cultural factors, social factors, personal factors, and psychological factors in decisions in choosing Batualambung Waterfall tourist attractions. The multiple linear regression equation is obtained Y = 0.261 + 0.178X1 + 0.936 X2 + 0.576X3 + 0.403X4. and have a significant effect either partially or simultaneously. Meanwhile, the close relationship between the variables of consumer behavior factors consisting of culture, social, personal, and psychology on the decision variables for the place is in the robust category, as well as the contribution or contribution of the independent variables of consumer behavior factors consisting of cultural, social, personal, and psychology on the decision variable to choose a place (Y) is 70.4%. The remaining 29.6% is caused by other factors not examined in this study, such as service quality and marketing mix.